THE EFFECT OF THINK PAIR SHARE STRATEGY AND STUDENTS’ READING MOTIVATION TOWARD STUDENTS’ READING COMPREHENSION AT SECOND SEMESTER STUDENTS OF LAW FACULTY UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU - Elva Utami; Yuneva Yuneva (English Language Teaching and Research, 2018)
This study was conducted to find out the effect of Think Pair Share (TPS) strategy and reading motivation on students’reading comprehension. This research was an experimental research. The population of the research was the second semester students of law faculty Universitas Prof. Dr. Hazairin, SH Bengkulu. There were six classes which consisted of 185 students. This research used cluster random sampling. This research data was obtained from reading comprehension tests and students’ reading motivation questionnaires. T-test analysis was used to analyze the data.  The findings of this study indicated that (1) Think Pair Share (TPS) strategy have a significant effect on students' reading comprehension  compared to conventional strategy commonly used by teacher in teaching reading, (2) Students with high reading motivation taught by Think Pair Share (TPS) Strategy has a better reading comprehension compared to what is taught with conventional strategy (3) Students with low reading motivation taught by Think Pair Share (TPS) Strategy were better than students taught with conventional strategy. Key words           : think pair share strategy, reading motivation, students’ reading  comprehension